PENAMBAHAN PREKURSOR KARNITIN (METIONIN & LISIN) DALAM RANSUM UNTUK MENINGKATKAN PERFORMANS DAN MENURUNKAN KADAR LEMAK AYAM BROILER - Abrani Sulaiman; Jauhar Fuady (Bioscientiae, 2008)
A research was conducted in order to investigate the effects of supplementing methionineand lysine as carnitin precursor in feed on the performances and fat contain of broiler chickens.Completely randomized design, 4 treatments and 4 replications (total 32 male chickens) wasutilized in the experiment. Control feed (meet NRC recommendation) and water were provided adlib during experiment (43-days). Treatments used in the experiment started at 22-days of age wereR0 (Control Feed), R1 (Control Feed + carnitin precursor type A (L-HCl Lysin 0,50 % + DLMethionine0,57 %)), R2 (Control Feed + carnitin precursor B (L-HCl Lysine 2 % + DLMethionine0,57 %)), and R3 (Control Feed + carnitin precursor C (L-HCl Lysin 1,50 % + DLMethionine0,19 %)). Data were gathered as parameters including body weight, growth rate, feedconsumption, feed conversion, carcass percentage, abdominal fat, and cholesterol contain. Datawas analyzed used ANOVA, then DMRT. Results show that supplementing methionine andlysine as karnitin precursor in feed affected increasing body weight and growth rate, decreasingfeed consumption, abdominal fat and cholesterol contain, but it did not affect feed conversion andcarcass yield. Based on results, the treatment R2 carnitin precursor B can be recommended as bestchoice feed for reducing abdominal fat and cholesterol contain but still produce high carcass yieldand feed efficiency.